Kinetics and Mechanism of Ruthenium(III) Catalyzed Oxidation of Phenyl Acetic Acid by Sodium-N-Chlorobenzene Sulphonamide (Chloramine-B) in Acid Solution - Kondarasaiah, M.H.; Ananda, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of phenyl acetic acid by chloramine-B (CAB) has been studied in hydrochloric acid solution at 303 K. In the absence of Ru(III) the rate shows a first order dependence on [CAB], independent with respect to [substrate] and first order dependence on [H+]. In presence of Ru(III), the rate is first order with respect to [CAB], independent with respect to [substrate], first order dependence on [H+] and fractional order dependence on [Ru(III)). The variation of the ionic strength, dielectric constant of the medium and addition of chloride ion, the reaction product of CAB (benzene sulphonamide) do not have significant effect on the reaction rate. The rate of oxidation of phenyl acetic acid by CAB has been studied for various concentrations of [Ru(III)] at different temperatures and the catalytic constants have been calculated. Activation parameters have been evaluated from Arrhenius plot. A mechanism consistent with experimental results has been proposed.